STUDI LITERATUR PEPTIDA MARKER UNTUK IDENTIFIKASI DERIVAT BABI PADA BERBAGAI PRODUK PANGAN - Jilan Salsabila Auliya Putri; Taufik Muhammad Fakih; Farendina Suarantika (UNISBA Press, 2023)
Abstract. One of the halal concepts in Islam states that food cannot contain even the smallest pork derivatives. Manufacturers often do not inform consumers about substitution of raw materials or other additives. Thus, it is necessary to verify whether the food circulating in the market contains pork or not. Identification can be carried out using peptide markers from pork derivatives in food products. The method used in this research is SLR (systematic literature review) with reference to articles on peptide markers for identification of swine derivatives. The data used is accessed through Pubmed, Science Direct, Springer, Oriental Journal of Chemistry, Theory and Practice of Meat Processing. The types of samples used are raw pork, processed pork products, and pork gelatin. Potential peptide markers in meat species identification are often obtained from myoglobin (Mb) and myosin (My). Because there are physiological differences in the specific protein content between different types of muscle tissue that can be detected in meat products after food processing is applied. Thus, the most commonly found peptide marker of myoglobin has the amino acid sequence YLEFISEAIIQVLQK and the peptide marker of myosin-1 which is most commonly found has the amino acid sequence SALAHAVQSSR. Most of the methods that can be used to identify peptide markers in pig derivatives are the development of mass spectrophotometry-based methods, namely liquid chromatography-mass spectrophotometry (LC-MS/MS). Abstrak. Salah satu konsep halal dalam Islam menyatakan bahwa bahan pangan tidak boleh mengandung derivat babi yang paling kecil sekalipun. Produsen seringkali tidak menginformasikan kepada konsumen mengenai substitusi bahan baku atau bahan tambahan lainnya. Sehingga, perlu dilakukan verifikasi apakah makanan yang beredar di pasaran mengandung babi atau tidak. Identifikasi dapat dilakukan dengan menggunakan peptida marker dari derivate babi pada produk pangan. Metode yang digunakan dalam penelitian ini adalah SLR (systematic literature review) dengan bahan menggunakan referensi artikel mengenai peptida marker untuk identifikasi derivat babi. Data yang digunakan diakses melalui Pubmed, Science Direct, Springer, Oriental Journal of Chemistry, Theory and Practice of Meat Processing. Jenis sampel yang digunakan yaitu berupa daging babi mentah, produk olahan daging babi, serta gelatin babi. Peptida marker potensial dalam identifikasi spesies daging sering didapatkan dari myoglobin (Mb) dan myosin (My). Karena terdapat perbedaan fisiologis dalam isi protein spesifik antara berbagai jenis jaringan otot yang dapat dideteksi pada produk daging setelah pengolahan makanan diterapkan. Dengan demikian, peptida marker dari myoglobin yang paling banyak ditemukan memiliki urutan asam amino YLEFISEAIIQVLQK dan peptide marker dari myosin-1 yang paling banyak ditemukan memiliki urutan asam amino SALAHAVQSSR. Metode yang dapat digunakan untuk identifikasi peptida marker pada derivat babi ini mayoritas dengan pengembangan metode berbasis spektrofotometri massa yaitu liquid chromatography-mass spectrophotometry (LC-MS/MS).